Hubungan Data Literacy dan Keterampilan Pemecahan Masalah Sosial pada Mahasiswa Calon Guru - Fajar Setiawan; Saktian Dwi Hartantri; Ilmawati Fahmi Imron; Nanang Khoirul Umam (Universitas Indraprasta PGRI, 2025)
The importance of evidence-based (data-driven) social problem-solving skills that prospective teachers must master requires adequate data literacy. This study aims to analyze the relationship between data literacy and social problem-solving skills in PGSD students. The research method uses a quantitative correlational approach to analyze the relationship between data literacy and social problem-solving skills in PGSD students. Data collection techniques included data literacy and social problem-solving skills tests, which were analyzed using Spearman's rho correlation test. The results showed that (1) the level of data literacy (mean = 80.6; SD = 9.94) and social problem-solving skills (mean = 80.9; SD = 9.68) were in the good category; and (2) There is a very strong positive correlation between data literacy and social problem-solving skills (ρ = 0.989; p < 0.001). These findings highlight the importance of incorporating data literacy and social problem-solving skills into the PGSD curriculum to prepare prospective teachers to become competent, responsive, and evidence-based agents of change.